2022
DOI: 10.1001/jamanetworkopen.2022.42221
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Withholding Perioperative Hydrocortisone for Patients With Pituitary Adenomas With an Intact Hypothalamus-Pituitary-Adrenal Axis

Abstract: ImportancePituitary adenoma is the second most common primary brain tumor. Perioperative hydrocortisone has been used for decades to avoid postoperative adrenal insufficiency. Recent studies suggest that withholding perioperative hydrocortisone may be safe for patients with an intact hypothalamus-pituitary-adrenal (HPA) axis.ObjectiveTo assess the safety of withholding hydrocortisone during the perioperative period of pituitary adenoma surgery for patients with an intact HPA axis.Design, Setting, and Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A recent, triple-masked, randomized clinical trial showed that the incidence of new-onset adrenal insufficiency directly after surgery was 11% (95% CI 6.9-15.2%) in the non-hydrocortisone group compared to 6.4% (95% CI 3.2-9.7%) in the hydrocortisone group which did not reach statistical significance. In a subgroup analysis of patients with a BMI < 25.5 kg/m 2 there was a significant difference in post-operative adrenal insufficiency [16]. In this study the reduction of hydrocortisone related complication of diabetes together with incidence of new-onset hypokalemia, hypernatremia and hypocalcemia was reduced by withholding hydrocortisone whereas incidence of hyponatremia was significantly increased by withholding treatment.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…A recent, triple-masked, randomized clinical trial showed that the incidence of new-onset adrenal insufficiency directly after surgery was 11% (95% CI 6.9-15.2%) in the non-hydrocortisone group compared to 6.4% (95% CI 3.2-9.7%) in the hydrocortisone group which did not reach statistical significance. In a subgroup analysis of patients with a BMI < 25.5 kg/m 2 there was a significant difference in post-operative adrenal insufficiency [16]. In this study the reduction of hydrocortisone related complication of diabetes together with incidence of new-onset hypokalemia, hypernatremia and hypocalcemia was reduced by withholding hydrocortisone whereas incidence of hyponatremia was significantly increased by withholding treatment.…”
Section: Discussionmentioning
confidence: 48%
“…In all of our patients, hydrocortisone was administered perioperatively (50 mg one hour before surgery and two subsequent dosages of 50 mg that same day, 75 mg intravenously on POD1, 20 mg orally on POD2) including those without preoperative adrenal insufficiency. Perioperative glucocorticoid supplementation has been the standard of care for a long period of time [16]. There is, however, debate whether this protocol is still necessary [1].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, perioperative glucocorticoid supplementation has long been a routine practice for patients with pituitary adenomas (Hattori et al., 2021 ; Molitch, 2017 ). A recent randomized clinical trial indicated that withholding hydrocortisone was safe and noninferior to the conventional hydrocortisone supplementation regimen regarding the incidence of new‐onset adrenal insufficiency among patients with an intact hypothalamic‒pituitary‒adrenal axis undergoing pituitary adenomectomy (Guo et al., 2022 ). However, researchers did not take postoperative delirium into consideration in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of these therapies is to attain biochemical control, and treatment risks vary based on the specific medication. Considering that these therapies might be prolonged or indefinite, understanding patient tolerability is essential [14].…”
Section: The Exceptions: Pituitary Adenomas and The Alternative Treat...mentioning
confidence: 99%
“…Furthermore, some pituitary adenomas may overproduce one or more hormones, resulting in hormonal imbalances that affect body functions, even when the tumors are small. Importantly, pituitary adenomas can occur in individuals of any age [14].…”
Section: Pituitary Adenomas 21 Introductionmentioning
confidence: 99%